Pyrazole synthesis via a cascade Sonogashira coupling/cyclization of N-propargyl sulfonylhydrazones. Issue 2 (11th December 2017) - Yang, Ying; Hu, Zi-Lin; Li, Ren-Hao; Chen, Yi-Hui; Zhan, Zhuang-Ping
Abstract : An efficient approach for the preparation of pyrazoles via a Pd(ii )/Cu(i )-catalyzed Sonogashira coupling/cyclization of N -propargyl sulfonylhydrazones has been established. Abstract : An efficient approach for the preparation of pyrazoles via a Pd(ii )/Cu(i )-catalyzed Sonogashira coupling/cyclization of N -propargyl sulfonylhydrazones has been established. In this study, we firstly report the strategic use of a Sonogashira reaction to construct pyrazole rings in a one step operation. With a broad range of functional group tolerance, bioactive 3-CF3 pyrazoles can also be synthesized easily through this domino coupling/cyclization sequence.